Teachers Questioning Techniques for Classroom Interaction In English Speaking Class - Erna Irmayanti; Andi Rustandi (Journal of English Education Program (JEEP), 2017)
ABSTRACTEnglish is a main subject in Chinese English classes, which requires plenty of practice, needscooperation between theteacher and students in class to jointly fulfill the verbalcommunication and the teaching-learning procedure. Classroom questioning, the skill of theelicitation method of teaching that is student-oriented and advocated today, gives an incentiveto communicative activities in English. Raising questions effectively is a major method of theteacher who guides his students to think actively, fostering students’ ability of analysis andcreation. It is also an essential way for the teacher to output information and obtain feedback,and an important channel to exchange ideas between the teacher and students. Therefore, theteacher must pay great attention to the skill of asking questions in English class. Eachquestion must be presented to accomplish the teaching objective and task. Only in this waymay the English teachers ask question effectively and improve the skill of questioning so asto make contribution to our Chinese English education. To begin with some elementaldefinitions, this paper discusses some basic knowledge of questions, and then explores theskill of questioning in English class about the preparing, designing, controlling andevaluating of questioning. Finally the benefit of the skill is studied with abundant teachingcases. The paper analyzes tentative in English class by integrating theory with practice. Thus,the skills of questioning are further understood in English classes.Keywords: English teaching, Questioning, Skills, Interaction teaching.